Impact of Singapore, US and Japanese macroeconomic shocks on Malaysian economy: a sign-restricted SVAR analysis - Mohd Azlan Shah Zaidi; Zulkefly Abdul Karim (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper examines the relative importance of Singapore, US and Japanese macroeconomic shocks on Malaysian economy. Employing structural vector auto regression (SVAR) model with a sign restriction approach, the study estimates four models. Each model consists of four domestic macroeconomic variables (output, inflation, interest rate and exchange rate) and three foreign variables (output, inflation and interest rate) of US, Japan, Singapore and the all countries trade-weighted variables, respectively. The results of the study reveal that, relative to domestic shocks, foreign shocks appear to play more prominent role in influencing domestic macroeconomic variables. Among the three foreign countries being investigated, the effect of shock of Singapore is the most dominant. The US effect comes second and the Japanese effect comes last. When Singapore’s variables are the only foreign factors in the system, their shocks bring about significant variation to Malaysian variables especially the output. Consequently, in modeling the effect of foreign factors on Malaysian economy, Singapore effect should be taken into account. This is important as Singapore is not only one of Malaysia’s long-term major trading partners, but it is also one of the Malaysia’s closest neighbors by geographical distance.